An android-based mobile educational game for disaster preparedness: an input to risk reduction management - Gene Marck Bañares Catedrilla; Jefferson Llobit Lerios; Sherwin Banaag Sapin; Manuel C Lanuang; Chester Alexis C Buama (Indonesian Journal of Electrical Engineering and Computer Science, 2021)
The Philippines is one of the countries in the world who suffers in different disasters, particularly natural disasters. Every year, there are more than twenty incidents recorded in the country related to different disasters which involve numerous lives of its citizens. It is found that most Filipinos have lack of knowledge in terms of disaster preparation specially, teenagers. This paper intended to develop a mobile-based game that aims to spread awareness on what to do during disasters. Upon development, forty-five (45) respondents were chosen to test the reliability of the application which composed of elementary students, household owners, police officers, fire fighters and IT experts. Further, ISO 25010 was adapted and modified in assessing the project. The results showed that the application is strongly acceptable and gives appropriate output in terms of disaster preparation garnering a total mean of 3.83